A solution algorithm for calculating the preload of T-type clamp bolts based on multiphysics coupling - Yuening Yang; Yuhang Ou; Rui Lin; Zifan Ding; Han Zhang; Yi Liu (PLoS ONE, 2026)
Under live-working conditions in distribution networks, the electric, magnetic, and thermal fields generated by current-carrying conductors inevitably affect the contact pressure between the conductor and the connecting fitting, thereby influencing the bolt preload of the fitting. Therefore, this study focuses on evaluating bolt preload in T-type clamps and investigating the influence of current under live-working conditions on that preload. A multiphysics coupling-based approach is proposed for the accurate determination of bolt preload in T-type clamps. First, the governing equations and boundary conditions for the bolt preload of the T-type clamp are derived based on elastic mechanics theory. Then, an iterative coupled electro–magneto–thermal multiphysics model is established, and the governing equations and boundary conditions for bolt preload, accounting for current-carrying effects, are derived. Finally, the preload equations are solved using the finite element method, enabling accurate evaluation of bolt preload under live-working conditions. A comparative analysis between experimental and simulation results is also conducted. Compared with experimental results from the Zhejiang Shangjian Electric Power Testing Institute, the proposed method has an average error of 5.82%. In comparison with methods that neglect multiphysics coupling, the average error is reduced by 11.41%. The proposed method enables an accurate determination of bolt preload in T-type clamps under live-working conditions in distribution networks.